2021
DOI: 10.1186/s12886-021-02014-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological findings of childhood ocular trauma in a public hospital in Colombia

Abstract: Background Eye injury is a serious worldwide public health problem that may cause blindness. In children, blindness has functional impact and psychosocial implications. As indicated in many worldwide studies, identification of risk factors associated with the socio-cultural context may prevent eye injuries. The objetive of the study is to describe the sociodemographic and epidemiological characteristics of pediatric eye injury and its effects on ocular structures in a public hospital from Colom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…13 The proportion of open globe injuries was 2.1-39% depending on the place of occurrence and treatment facility. 5,13,[17][18][19][20][21] Studies conducted in eye casualty centers, tertiary institutions, and developing nations demonstrated a higher rate of open globe injury 5,[17][18][19][20][21] than a study done in an ED. 13 In the present study, the rate of open globe injury was only 0.4%.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…13 The proportion of open globe injuries was 2.1-39% depending on the place of occurrence and treatment facility. 5,13,[17][18][19][20][21] Studies conducted in eye casualty centers, tertiary institutions, and developing nations demonstrated a higher rate of open globe injury 5,[17][18][19][20][21] than a study done in an ED. 13 In the present study, the rate of open globe injury was only 0.4%.…”
Section: Discussionmentioning
confidence: 90%
“…A prospective study revealed that age greater than10 years, pre‐existing refractive error, impact with a blunt object, and open globe injury were risk factors for poor ophthalmological outcomes 13 . The proportion of open globe injuries was 2.1–39% depending on the place of occurrence and treatment facility 5,13,17–21 . Studies conducted in eye casualty centers, tertiary institutions, and developing nations demonstrated a higher rate of open globe injury 5,17–21 than a study done in an ED 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penetrating ocular injuries is a major type of OGI that can cause severe visual impairment [ 1 , 11 ]. The epidemiological statistics of penetrating ocular trauma have been reported in developed countries such as the USA [ 3 , 12 14 ], Europe [ 15 ] and Australia [ 16 ], and some developing countries including India, Iran, and Egypt [ 9 12 ]. Although the statistical data on ocular trauma in several southern provinces of China are available, the statistics on ocular trauma in China are still insufficient [ 1 , 4 , 17 ].…”
Section: Introductionmentioning
confidence: 99%